Variation in Uteroglobin-Related Protein 1 (UGRP1) gene is associated with Allergic Rhinitis in Singapore Chinese - Wang De Yun; Suri Bani; Anantharaman Ramani; Parate Pallavi; Yeo Wei; Andiappan Anand; Chew Fook (BMC, 2011)
Abstract Background Uteroglobin-Related Protein 1 (UGRP1) is a secretoglobulin protein which has been suggested to play a role in lung inflammation and allergic diseases. UGRP1 has also been shown to be an important pneumoprotein, with diagnostic potential as a biomarker of lung damage. Previous genetic studies evaluating the association between variations on UGRP1 and allergic phenotypes have yielded mixed results. The aim of this present study was to identify genetic polymorphisms in UGRP1 and investigate if they were associated with asthma and allergic rhinitis in the Singapore Chinese population. Methods Resequencing of the UGRP1 gene was conducted on 40 randomly selected individuals from Singapore of ethnic Chinese origin. The polymorphisms identified were then tagged and genotyped in a population of 1893 Singapore Chinese individuals. Genetic associations were evaluated in this population comparing 795 individuals with allergic rhinitis, 718 with asthma (of which 337 had both asthma and allergic rhinitis) and 717 healthy controls with no history of allergy or allergic diseases. Results By resequencing the UGRP1 gene within our population, we identified 11 novel and 16 known single nucleotide polymorphisms (SNPs). TagSNPs were then genotyped, revealing a significant association between rs7726552 and allergic rhinitis (Odds Ratio: 0.81, 95% Confidence Interval: 0.66-0.98, P = 0.039). This association remained statistically significant when it was analyzed genotypically or when stratified according to haplotypes. When variations on UGRP1 were evaluated against asthma, no association was observed. Conclusion This study documents the association between polymorphisms in UGRP1 and allergic rhinitis, suggesting a potential role in its pathogenesis.